2016
DOI: 10.1016/j.cattod.2015.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Strong metal-support interaction and alloying in Pd/ZnO catalysts for CO oxidation

Abstract: Pd/ZnO catalysts with different Pd content have been synthesized, thoroughly characterized and investigated with regard to their reduction behavior in hydrogen or carbon monoxide containing atmospheres, by applying CO-chemisorption, photoelectron spectroscopy, X-ray diffraction, electron microscopy, TPR and DRIFTS techniques. As a catalytic test reaction, CO-oxidation has been applied. The interaction of the noble metal with the support has been revealed in a way that can distinguish between alloying and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 40 publications
5
36
0
Order By: Relevance
“…22 Depending on the thermal treatments and gas atmospheres, the formation of αand/or β-PdZn and AuZn alloys and intermetallic structures, as well as the presence of strong-metal support interaction (SMSI) states, have been reported. [16][17][18][23][24][25][26] Zn incorporation seems to change the number of ensemble active atoms as well as the Pd or Au electronic properties due to charge transfer between Zn and the metal, consequently affecting the catalytic behaviour. In addition, the catalytic performance of PdZn and AuZn phases seem to be influenced by the exposed ZnO facets.…”
Section: Introductionmentioning
confidence: 99%
“…22 Depending on the thermal treatments and gas atmospheres, the formation of αand/or β-PdZn and AuZn alloys and intermetallic structures, as well as the presence of strong-metal support interaction (SMSI) states, have been reported. [16][17][18][23][24][25][26] Zn incorporation seems to change the number of ensemble active atoms as well as the Pd or Au electronic properties due to charge transfer between Zn and the metal, consequently affecting the catalytic behaviour. In addition, the catalytic performance of PdZn and AuZn phases seem to be influenced by the exposed ZnO facets.…”
Section: Introductionmentioning
confidence: 99%
“…For Pd/SiO 2 (c), two distinct bands are observed at 2087 and 1930 cm −1 , corresponding to linearly bonded (2080‐2100 cm −1 ) and bridge bonded CO (1900‐1965 cm −1 ), respectively . For PdZn 6 /SiO 2 (c), the linearly bonded CO is shifted towards shorter wavelength (2076 cm −1 ), suggesting the electronic effect in the PdZn alloy . For PdCu 6 /SiO 2 (c), the linearly CO bond is shifted towards higher wavelength (2118 cm −1 ), which also indicates the electronic modification in the PdCu alloy .…”
Section: Resultsmentioning
confidence: 93%
“…Figure shows the infrared spectra of CO adsorbed on PdM 6 /SiO 2 (c). For Pd/SiO 2 (c), two distinct bands are observed at 2087 and 1930 cm −1 , corresponding to linearly bonded (2080‐2100 cm −1 ) and bridge bonded CO (1900‐1965 cm −1 ), respectively . For PdZn 6 /SiO 2 (c), the linearly bonded CO is shifted towards shorter wavelength (2076 cm −1 ), suggesting the electronic effect in the PdZn alloy .…”
Section: Resultsmentioning
confidence: 97%
“…The effects of interfaces on catalytic properties have been investigated in many cases. If we take CO oxidation as an example, Pt/ m ‐Co 3 O 4 catalysts, Pd/nanodiamond‐graphene core–shell materials, and Pd/ZnO catalysts exist with 1 D or 2 D metal–support interfaces. Zheng et al.…”
Section: Introductionmentioning
confidence: 99%
“…The effectso fi nterfaces on catalytic properties have been investigated in many cases. If we take CO oxidation as an example, Pt/m-Co 3 O 4 catalysts, [16] Pd/nanodiamond-graphene core-shell materials, [17] and Pd/ZnO catalysts [18] exist with 1D or 2D metal-support interfaces. Zheng et al reported iron-nickelh ydroxideplatinum nanoparticles that were highly efficient for CO oxidation at room temperature because of the abundants ites for Pt-OH-M interfaces.…”
Section: Introductionmentioning
confidence: 99%